Implementasi Kebijakan Program Siaran Berita Sulawesi Utara Hari Ini (Studi Di Tvri Sulawesi Utara) - Lumingkewas, Chetiza; Kawung, Evelin; Mingkid, Elfie (AGRI-SOSIOEKONOMI, 2023)
This study aims to determine the policy implementation of the Sulawesi Utara Hari Ini’s news program on TVRI North Sulawesi. This research was conducted from January to March 2023. This research used a qualitative design with descriptive analysis, in order to be able to reveal, describe, and understand the phenomena that occur in the setting and object of research. The research focus consists of communication, resources, attitudes/dispositions, and bureaucratic structure based on the policy dimensions of George Edward III. The results showed that the communication between team leaders and news contributors was not effective due to the lack of face-to-face meetings, the lack of human resources in the news unit so that officers held multiple jobs, the disposition did not yet have a standard reward and punishment standard for news unit employees, and bureaucratic structure There is no detailed organizational structure regarding the 14 news unit professions, so that the implementation of policies and standard operating procedures in the news unit for Sulawesi Utara Hari Ini broadcast program must be maximized.